Letter to Editor - Dr Sunil Kumar (Pediatric Review: International Journal of Pediatric Research, 2018)
The case report is very abridged. The phenotypic features of child whether fitting into those described for children with Job’s Syndrome, detailed family history of other affected/suspected family members and evaluation for other features of Job’s Syndrome is missing.